New distribution data of orb-weaver spiders in Morocco (Araneae: Araneidae) - Gál, János; Robson, L.; Kovács, G. (Acta Agraria Kaposváriensis, 2016)
The authors collected and examined 11 species of 7 genera of the Araneidae family in Morocco between the 1st of June 2012 and the 31st of November 2013. These 11 species belong to the following genera: Agalenatea, Araneus, Argiope, Cyclosa, Cyrtophora, Larinioides and Zygiella. In this paper we add the first report on 10 of these species in the area of Morocco. Of all the taxa we found in Morocco only one - Araneus arganicola Simon, 1909 - was known from the country previously.
Keywords: Araneidae; faunistic data; spider; Morocco